Exploring the Role of Principal Behavior in Shaping Teacher Performance - Mohammad Rifa’i; Moh. Rofik (STAI Ma'had Aly Al-Hikam Malang, 2025)
This research aims to examine the role of the principal's behavior in shaping teacher performance at Nurul Jadid High School. The main focus of the research is to understand how principal behavior, such as effective communication, appreciation of teachers, and ongoing coaching, influences the quality of teacher work. This research uses quantitative methods with a survey approach. Data was collected through questionnaires distributed to teachers at Nurul Jadid High School, then analyzed using regression analysis to determine the relationship between principal behavior and teacher performance. The research results show that positive principal behavior, especially effective communication and giving appreciation, has a significant influence on improving teacher performance. Apart from that, structured coaching helps improve the quality of teaching. Participative leadership has also been proven to increase collaboration between teachers. The implications of this research emphasize the importance of school principals in creating a positive work environment to improve the quality of education. Recommendations are given to school principals to continue to build open communication, provide regular appreciation, and carry out ongoing coaching to support teacher professional development.